Mechanical and physical properties of kenaf fibre reinforced thermoplastic elastomer composites - Lingenthiran, Samylingam (2015)
This research was conducted to study the physical properties, mechanical properties and scanning electron microscope studies of reinforced kenaf fibre with TPE. Generally, the tensile and flexural properties of kenaf reinforced composites, vary depending on the type of fibre, its orientation (random or unidirectional), content and form (fibre or fabric), and the type of blending/plasticizer used. The kenaf fibre reinforced TPE composite developed by using the twin screw extruder with 200 ˚C and 50 rpm. The experiment for tensile strength, flexural strength, moisture content and water absorption test were conducted according to ASTM D638, ASTM D790, ASTM D1348, and ASTM D5229 respectively. The 30% of kenaf mixture exhibit highest mechanical properties where it has 31 GPa modulus of elasticity, 32 MPa of tensile strength, and 47 MPa of flexural strength. The 30% of kenaf mixture contain moisture of content 4.99%, absorbs 2.99% of water before heat treated, and 1.03% of water after heat treated.